Analysis of the Influence of Production, Global Prices, Exchange Rate, and Interest Rate on Changes in Indonesia’s Crude Palm oil (CPO) Export Value - Rasendriya Rahya Rabbani; Raden Parianom (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
Exports play a pivotal role in Indonesia’s economic growth, with crude palm oil (CPO) being a key contributor to international trade. A decline in CPO export value could potentially weaken economic performance. This study investigates the influence of production, global prices, exchange rates, and interest rates on Indonesia’s CPO export value using the Error Correction Model (ECM) for the 1995–2024 period. The findings indicate that production has a significant positive impact on export value in both the short run and the long run. Global prices and exchange rates also exert significant effects across both horizons, while domestic interest rates show an indirect influence. Overall, the study confirms that Indonesia’s CPO export dynamics are shaped by a combination of production factors and macroeconomic variables, with distinct patterns of relationship between short-run and long-run contexts.